Does the Inclusion of Robots Affect Engineering Students’ Achievement in Computer Programming Courses? - Özüorçun, Nilcan Çiftçi; Bicen, Hüseyin (Eurasia Journal of Mathematics, Science and Technology Education, 2017)
Applied courses are difficult to teach to undergraduate engineering students in classical classrooms. To facilitate students’ understanding and capture their motivation, technology should be incorporated into classrooms. In the Engineering Faculty, there are courses that are difficult to learn in a classical classroom and laboratory sessions; the programming algorithm course is one such class. Educational robots are required for teaching and learning programming algorithm logic. The Lego Mindstorms EV3 robots represent excellent technology to teach programming algorithm course subjects. The important point about the programming algorithms course is that it enables understanding of the logic of programming, as it enhances students’ understanding of what it means when they are coding. This paper investigates how engineering faculty students’ achievements are affected by robotics technology when learning computer programming algorithm logics. It analyses a usable solution with the Lego Mindstorms EV3 robot in the engineering classrooms for the introduction to computer programming course. The statistical results showed, Lego robot usage has raised student achievement in the introduction to computer programming course.